Comprehensive study on structural, elastic and radiation shielding abilities of novel quaternary Bi2O3–TeO2–Li2O–Al2O3 glasses - Shah, Aishah Zarzali; Mohd Zaid, Mohd Hafiz; Matori, Khamirul Amin; Yaakob, Yazid; Sarmani, Abdul Rahman; Hisam, Rosdiyana (Elsevier, 2024)
Novel quaternary glasses with varying compositions of xBi2O3-(75–x)TeO2–20Li2O–5Al2O3 were synthesized using a melt-quenching method to analyze their physical, elastic properties and to evaluate their potential as radiation shielding materials. The X-Ray Diffraction (XRD), Fourier Transform Infrared (FTIR) and ultrasonic measurement were utilized to study those properties. The radiation shielding properties of the glass samples were determined for 0.01–10000 MeV photon energy range by using Phy-X/PSD software. The incorporation of Bi2O3, ranging from 0 mol% to 5 mol%, led to an increase in density which is measured by Archimedes’ principle, ascending from 4.68 to 5.06 g/cm3 . The longitudinal, bulk, shear, and Young’s modulus, displayed a non-linear decline from 63.41 to 61.44 GPa, 33.52 to 33.20 GPa, 22.41 to 21.18 GPa, and 54.99 to 52.39 GPa. Furthermore, the inclusion of Bi2O3 up to x = 5 mol% produce mass attenuation coefficient (MAC) of 14.892 cm2/g at x-ray energy of 40 KeV, surpassing that of commercial RS360 and RS520 radiation shielding glasses by 577% and 323%, respectively. When subjected to gamma ray of 662 KeV the MAC is 0.08 cm2/g which was also accompanied by a reduction in the half-value layer (HVL) to 1.58 cm where it surpassed the concrete by 38% and linear attenuation coefficient (LAC) of 0.38 cm−1. The effective atomic number (Zeff) and effective electron density (Neff) reach maximum value of 59.74 and 7.88 × 1023 electrons/g at 0.02 MeV respectively. These results highlight the suitability of the glass composition with x = 5 mol% as an exceptional choice for employment as to shield against both X-rays and gamma rays.